Arginine, symmetric and asymmetric dimethylarginine levels in canine leishmaniasis. (May 2023) - Gultekin, Gamze; Pasa, Serdar; Ural, Kerem; Erdogan, Hasan; Gonulveren, Gizem; Gultekin, Mehmet
Abstract: The study aimed to investigate the levels of arginine, symmetric dimethylarginine (SDMA), and asymmetric dimethylarginine (ADMA) in dogs with canine leishmaniasis (CanL) and their relationship with some renal and cardiovascular parameters. A total of 60 dogs were enrolled, including 40 with CanL and 20 healthy controls. The CanL group was divided into four stages based on clinical and laboratory findings. The levels of plasma arginine, SDMA, and ADMA were determined by high performance liquid chromatography (HPLC). The data from the healthy group were compared with those from the CanL group, and according to the stages. In dogs with CanL, systolic and diastolic blood pressure, plasma creatinine, cystatin-C, phosphorus, potassium, and low-density lipoprotein concentrations, the urine protein/creatinine ratio, the amount of nitric oxide, and creatine kinase-MB activity were higher, while the high-density lipoprotein concentration was lower compared to healthy controls. The concentration of arginine was low (p < 0.05) and the levels of ADMA (p < 0.001) and SDMA (p < 0.05) were high in dogs with CanL. There were no statistically significant differences in arginine concentration among the different stages of CanL. However, the concentration of plasma ADMA was higher in all stages of CanL compared to the healthy group, and the concentration of plasma SDMA was higher in Stage IV compared to the healthy group and Stage III. The present study demonstrates for the first time a decrease in arginine concentration and an increase in ADMA concentration in dogs with CanL. The increase in SDMA concentration in dogs with CanL was consistent with previous studies. However, compared to other renal parameters, SDMA exhibited limited performance distinguishing between clinical stages of CanL. These findings could be a source for future diagnostic and therapeutic studies to explain the renal and cardiovascular pathophysiology of CanL. Additional clinical studies that include treatment and patient follow-up with an assessment of the acute phase response are needed to provide a more detailed understanding of the changes observed in dogs with CanL. Highlights: Arginine and dimethylarginine levels were analyzed with High-Performance Liquid Chromatography. Dogs with canine leishmaniasis had low arginine and high dimethylarginine concentrations. These findings suggest a relationship between arginine metabolism impairment and canine leishmaniasis.